Diseño de estratégias para la enseñanza del mini básquet en los niños de séptimos años de la escuela Federico Gonzalez Suárez del cantón Salcedo, provincia de Cotopaxi en el año lectivo 2013-2014 - Fernández Laguaquiza, Sandro Francisco (2016)
The purpose of this study is the presentation of a proposal for the learning of mini basketball for the student of the Seventh years Federico González Suárez School Canton Salcedo in the 2013-2014 school years, whose main objective is to analyze the theoretical foundations and concept for teaching mini basketball to strengthen physical skills in children. In developing the proposed work will be described for excellent learning about mini basketball, will take place under a descriptive methodology, framed from the point of view according to the projective and prospective field study….